SPECIAL FEATURES OF ROMAN SERVITUDES - Esin Kranli Bajram (Faculty of law iustinianus Primus skopje, 2018)
The main goal of this article is to present the position, as well as the some of the most important characteristics of the roman servitudes. Having on mind the fact that they can be related to the modern types of servitudes, this article gives a detailed explanation of the ancient roman jurists’ idea how to incorporate the servitudes in the system of the property law. Therefore in this occasion are especially noted the similarities as well as differences between the property-legal institutes, and main principles of Roman servitudes.